DEVELOPMENT OF CREATIVITY IN LEARNING LABORATORY ACTIVITIES IN INFORMATION TECHNOLOGY (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
This article focuses on increasing creativity in the study of laboratory activities in the science of information technology. The formation of creative abilities is considered one of the urgent problems of today, and the improvement of creative abilities is taken into account in the study of laboratory exercises.